2021
DOI: 10.1111/bjop.12546
|View full text |Cite
|
Sign up to set email alerts
|

Objects that induce face pareidolia are prioritized by the visual system

Abstract: The human visual system has evolved specialized neural mechanisms to rapidly detect faces. Its broad tuning for facial features is thought to underlie the illusory perception of faces in inanimate objects, a phenomenon called face pareidolia. Recent studies on face pareidolia suggest that the mechanisms underlying face processing, at least at the early stages of visual encoding, may treat objects that resemble faces as real faces; prioritizing their detection. In our study, we used breaking continuous flash su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…As some researchers expect higher face pareidolia rates in SZ patients who are considered to be prone to hallucinations 79 , 81 , we compared face response rates in SZ patients who self-reported hallucinations and who did not. With canonical upright orientation, face pareidolia rates did not differ between these sub-groups (with hallucinations, 0.54 ± 0.18; without, 0.48 ± 0.21; t (20) = 0.02, p = 0.490, two-tailed, n.s.).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As some researchers expect higher face pareidolia rates in SZ patients who are considered to be prone to hallucinations 79 , 81 , we compared face response rates in SZ patients who self-reported hallucinations and who did not. With canonical upright orientation, face pareidolia rates did not differ between these sub-groups (with hallucinations, 0.54 ± 0.18; without, 0.48 ± 0.21; t (20) = 0.02, p = 0.490, two-tailed, n.s.).…”
Section: Resultsmentioning
confidence: 99%
“…To date, a handful of studies on face pareidolia are available in SZ, and the outcome is controversial. It is shown that patients with SZ see face-like objects faster than non-face-like images 79 . In contrast, patients are reported either to identify fewer face-like images as faces 80 or exhibit higher face pareidolia scores 81 .…”
Section: Introductionmentioning
confidence: 99%
“…Face-pareidolia refers to the illusory phenomenon when typical subjects report face perceptions emerging from visual stimuli that do not physically contain any picture of a face. Albeit correlative evidence demonstrates that real face perception and face pareidolia share substantial neurophysiological features [37], [73]-[76], no causal evidence is available linking face-sensitive regions to face-pareidolia and, most importantly, linking speci c neurophysiological activities to illusory face perception. By entraining neural oscillations in the GBO range (40 Hz) with tACS, we here (i) demonstrate the involvement of the "core" and "extended" face networks in face pareidolia, as well as the (ii) causal role of GBO (i.e., 40 Hz) in illusory face perception.…”
Section: Discussionmentioning
confidence: 99%
“…The controversy around interpretations of the Hugh Gray photograph could be constructively leveraged to advance studies of individual differences in pareidolia, and especially how they influence bottom-up and top-down factors in perceptual processing (see e.g., Caruana & Seymour, 2021;Salge et al, 2021;Zhou & Meng, 2020). As noted earlier, confirmation biases and other confounds that promote pareidolia have been identified in believers of esoteric ideas or phenomena (Brugger, 2001;Drinkwater et al, 2020;Houran & Williams, 1998;.…”
Section: Implications and Applicationsmentioning
confidence: 97%